MiRNA-455-5p regulates the growth and development of adipose tissue by targeting IGF-1R gene - Min Wu; Lingli Feng; Yubin Wang; Kun Zhang; Ganqiu Lan; Jing Liang (Journal of Applied Animal Research)
Adipose tissue is an important factor that influences porcine quality, and adipose tissue is also an important endocrine regulator of metabolic homeostasis. Adipose tissue development involves a series of highly synergistic processes, including clone amplification, proliferation arrest and terminal differentiation. In recent years, microRNAs (miRNAs) are a class of non-coding endogenous RNA molecules that have been considered as a class of novel regulators of adipogenesis. In this study, we used the dorsal subcutaneous adipose tissue of Guangxi Bama mini-pigs and Landrace pigs as experimental materials to study the molecular mechanism of adipogenic differentiation of preadipocytes, and the regulatory mechanism of miRNA-455-5p and its target gene IGF-1R involved in the development of adipose tissue. These findings may improve our understanding of mechanism of the molecular regulation of miRNA-455-5p and IGF-1R in pigs, and provide a theoretical basis for increasing pork production.TEASER TEXT The miRNA-455-5p was involved in the negative regulation of adipose tissue development by inhibiting the expression of its target gene IGF-1R.ABSTRACT Adipose tissue is an organ with metabolic, endocrine and immune functions, affecting the life span of animals and their susceptibility to diseases. Previous studies have reported the relationship between many miRNAs and the development of adipose tissue. However, the regulation of miR-455-5p on the development of porcine adipose has not been reported. In this study, we used the dorsal subcutaneous adipose tissue of Guangxi Bama mini-pigs and Landrace pigs as experimental materials to study the regulatory mechanism of miRNA-455-5p and its target gene IGF-1R involved in the development of adipose tissue. Bioinformatic analysis with Targetscan predicted that IGF-1R might be a target gene of miRNA-455-5p. Moreover, mouse 3T3-L1 preadipocytes were transfected with chemically modified mimics and inhibitors to observe the expression of miR-455-5p and IGF-1R genes from 0 to 8 days after transfection. And the expression of adipogenic marker genes PPARγ and C/EBPα was examined. Additionally, the miRNA-455-5p may be involved in the negative regulation of adipose tissue development by inhibiting the expression of its target gene IGF-1R. These results provide a theoretical basis for increasing pork production and provide a new potential target for the treatment of obesity and type 2 diabetes in humans.